3-Amino-1-methyl-1H-pyridin-2-one as Inbuilt Directing Group for Additive-Free Late-Stage ortho-Amination under Copper Catalysis towards Biologically Relevant Molecules - Manna, Priyadarshi; Chatterjee, Arunima; Kundu, Mrinalkanti; Rao, G. Prabhakar; Mukherjee, Rusmita; Podder, Swarnali; Datta, Bandita; Adhikari, Susanta (Synthesis, 2025)
Arylamines are essential building blocks that are found in biologically important substances, agrochemicals, and natural products. One of the C–N bond formation methods that is conveniently step- and atom-economical is the C–H bond activated amination process. We divulge an operationally simple and general method using 3-amino-1-methyl-1H-pyridin-2-one (AMP) as inbuilt directing group (DG) for additive-free, copper(II)-catalyzed ortho amination of β-C(sp2)–H bonds of arenes and heteroarenes. Notably, this cross dehydrogenative amination reaction exhibits a broad scope regarding amine coupling partners, including heterocyclic amines, secondary aliphatic amines, and cyclic amides, with exclusive site selectivity and excellent functional group tolerance. Moreover, implementing this methodology, we could also synthesize medicinally important compounds to showcase the suitability of this inbuilt DG for late-stage functionalization.
Keywords: C(sp2)–H amination; amidation; external-ligand-free; additive-free; Cu(OAc)2 catalysis; late-stage functionalization